Profil Peredaran Kosmetik Tanpa Izin Edar (TIE) Di Provinsi Bengkulu Tahun 2025 - RR.Chrysna Winandha; Dewi Nopitasari; Hifdzi Ulil Azmi (Jurnal Pharmacopoeia, 2026)
Cosmetics are pharmaceutical products supervised by the Indonesian Food and Drug Authority (BPOM). In Bengkulu Province, cosmetics are sold in stores, salons, clinics, and traditional markets as well as online. Traditional markets primarily reach lower-middle-class consumers, who often exploit the lack of consumer awareness. Beauty clinics and cosmetic stores reach upper-middle-class consumers, who also have the potential for the distribution of cosmetics without a distribution permit (illegal) through purchases from unauthorized distribution channels. Meanwhile, the growth of the online market and the lack of oversight allow illegal cosmetics from marketplaces to be sold in stores and traditional markets. This study aims to describe the distribution profile of illegal cosmetics in Bengkulu Province through cosmetic distribution channels and traditional markets, as well as their relationship to online sales. The purpose of this study was to determine the distribution profile of illegal cosmetics in Bengkulu Province. The study was conducted by collecting oversight data of BPOM in Bengkulu through field inspections and freight forwarding services. The results showed that illegal cosmetics found in cosmetic distribution channels were dominated by skincare products (60.8%), which are categorized as imported and relabelled cosmetics with unknown hazardous ingredients. In traditional markets, the most commonly found illegal cosmetics are day creams (50.5%), lip makeup (37.5%), and night creams (6.9%), most of which contain the hazardous ingredient mercury. Online monitoring revealed that illegal cosmetics were dominated by day creams (33.8%), facial toners (25.4%), whitening (18.1%), and solid body wash (13.3%), all of which contain the hazardous ingredient mercury and a combination of retinoic acid and hydroquinone. This study concluded that traditional markets are at greatest risk of distributing illegal cosmetics containing hazardous ingredients.